Hardening of Metallurgical Machinery Components by Facing with Heatproof, Hard Steels and Low Temperature Pre-Heating; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Malushin N. N.; Valuev D. V. Denis Viktorovich; Osetkovsky V. L.; Valueva A. V. Anna Vladimirovna; Serikbol A. (Material Engineering and Technologies, 2015)
Title screen